Development of a Multi-Strategy Model for Rural Reduction of Poverty - Jamroni, Mofit; Amalia, Rizka; Ambayoen, Mas Ayu; Purnomo, Mangku; Siswantoro, Ajik; Sunarto, Bintar Probo; Ma'ruf, Zulfan Firdaus (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
Interrelated structural, social, and administrative factors still influence rural poverty in East Java. This activity aims to analyze the effectiveness of various approaches to poverty alleviation, develop an integrative model appropriate to the region's characteristics, and formulate recommendations for sustainable multi-strategy policies. Data collection was conducted through document studies, observations, and indept interview in three regency, Probolinggo, Blitar, and Nganjuk. The research results show that low agricultural productivity, limited market access, weak local economic institutions, dependence on social assistance, and inaccurate beneficiary data are the leading causes of rural poverty. Each region has a different context, ranging from mentalities and economic capacity barriers to infrastructure inequalities and data accuracy issues that trigger social conflicts. Based on these findings, a multi-strategy model was developed around three main pillars: sharpening fiscal and non-fiscal resources, integrating cross-sectoral programs with the same objectives, and filling program gaps through data strengthening and profession-based empowerment. The multi-strategy approach framework serves as a foundation to ensure that interventions are targeted and aligned with the real needs of the community. This recommendation model is expected to strengthen improve program effectiveness, and accelerate rural poverty reduction by increasing economic capacity and fostering more targeted policy synergies.